Evaluation of the Mutagenicity of Antimalarial products isolated from Solanum nudum (Solanaceae) (2003)
ABSTRACT: Diosgenone is a major component of the hexane extract from the plant Solanum nudum (Solanaceae). The products from degraded and acetylated diosgenone that showed in vitro antimalarial activity against the FCB-2 strain of Plasmodium falciparum and methanol, dichloromethane and ethereal extracts of Solanum nudum were tested for their mutagenic activity using the Ames test with the TA-97a, TA-98, TA-100 and TA-102 strains of Salmonella typhimurium. These compounds were not mutagenic at the tested concentrations.